Phosphate positive electrode material and preparation method and application thereof

By doping a variety of metal ions into the phosphate-based positive electrode material and adopting a low mesoporous carbon shell coated structure, the problem of the interface reaction between the positive electrode material and the electrolyte during the constant power cycle is solved, and the circulation stability of the material and the life of the battery are significantly improved.

CN119650629APending Publication Date: 2025-03-18SHENZHEN DYNANONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411751834.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing phosphate-based positive electrode materials react severely with the electrolyte during constant power cycle, resulting in shortening of lithium ion consumption and battery life, especially in high-temperature environments.

Method used

A phosphate-based active material doped with a variety of metal ions is used as the core and is coated by a carbon shell layer. The number of mesoporous and pore sizes on the outer surface of the carbon shell layer are lower than the number of mesoporous and pore sizes inside to reduce interface reactions.

Benefits of technology

By reducing interface reactions, the constant power cycle stability of the cathode material is improved, the battery life is extended and safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650629A_ABST
    Figure CN119650629A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a phosphate positive electrode material and a preparation method and application thereof. The phosphate positive electrode material comprises an active inner core and a carbon shell layer coating the outer surface of the active inner core, wherein the active core comprises a phosphate active material doped with various metal ions, and the number and aperture of mesopores in the outer surface of the carbon shell layer are lower than those of mesopores in the carbon shell layer. The doping of various metal ions improves the crystal stability, enhances the stability of the material body, improves the conduction rate of lithium ions, and improves the constant-power cycle stability of the positive electrode material. The outer surface of the carbon shell layer has few defects, few pores and high compactness, so that an electrolyte can be more effectively prevented from penetrating through the carbon shell layer to be in contact with the active core, the interface side reaction between the positive electrode material and the electrolyte and solvation of lithium ions are reduced, the loss of the lithium ions in the charge-discharge process is reduced, and the constant-power cycle stability of the positive electrode material is improved; the service life and the safety of the applied battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and in particular relates to a phosphate-based positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high single-cell output voltage, excellent cycle stability, environmental friendliness, fast charge and discharge, and long service life. They are widely used in electronic products, electric vehicles, and energy storage power systems of new energy power stations. The positive electrode material is one of the key factors affecting the performance of lithium-ion batteries.

[0003] The constant power cycle performance of positive electrode materials such as lithium iron phosphate is an important indicator to measure the quality of the material, especially in high temperature environments. During the constant power cycle process, the electrolyte will have a serious interface reaction with the material, consuming lithium ions, reducing the total amount of lithium ions used in the charging and discharging process, and seriously affecting the life of the battery. Especially when the battery is at high temperature, the side reaction rate is faster and the battery performance decay is more serious. Therefore, slowing down / preventing the interface reaction is one of the important research directions to improve battery performance.

[0004] At present, the above problems are mainly solved by coating modified cathode materials such as lithium iron phosphate with graphite carbon, using the better electronic and ionic conductivity of graphite carbon to make up for the poor conductivity of the cathode material itself. However, during the high-temperature pyrolysis and graphitization of the carbon source, the graphite layer will form smaller mesopores, and the electrolyte can pass through the mesopores to react with the cathode material, exacerbating battery degradation. Summary of the invention

[0005] The purpose of the present application is to provide a phosphate-based positive electrode material and a preparation method and application thereof, aiming to solve the problem of interface reaction between existing phosphate-based positive electrode materials and electrolytes, and reduce the constant power cycle performance of positive electrode materials to a certain extent.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In the first aspect, the present application provides a phosphate-based positive electrode material, comprising an active core and a carbon shell layer coated on the outer surface of the active core; wherein the active core contains a phosphate-based active material doped with multiple metal ions, and the number and pore size of mesopores on the outer surface of the carbon shell layer are lower than the number and pore size of mesopores inside.

[0008] In a second aspect, the present application provides a method for preparing a phosphate-based positive electrode material, comprising the following steps:

[0009] Obtaining a phosphate precursor material, and performing a sintering treatment under an inert atmosphere to obtain a sintered product; the sintered product includes a phosphate active core semi-finished product doped with multiple metal ions and a sintered carbon shell;

[0010] After the calcined product is mixed with oxygen-rich organic matter, a secondary sintering treatment is performed under an inert atmosphere to obtain a phosphate-based positive electrode material including an active core and a carbon shell; the number and pore size of mesopores on the outer surface of the carbon shell are lower than the number and pore size of mesopores inside.

[0011] In a third aspect, the present application provides a positive electrode sheet, including a current collector and a positive electrode active layer formed on the surface of the current collector, wherein the positive electrode active layer contains the above-mentioned phosphate-based positive electrode material.

[0012] In a fourth aspect, the present application provides a secondary battery comprising the above-mentioned positive electrode sheet.

[0013] The phosphate-based positive electrode material provided in the first aspect of the present application comprises an active core and a carbon shell, wherein the active core comprises a phosphate-based active material doped with a plurality of metal ions, and the doping of a plurality of metal ions can improve the crystal stability, enhance the stability of the phosphate-based active material body, and improve the conduction rate of lithium ions inside the positive electrode material, which is beneficial to improve the constant power cycle stability of the positive electrode material. The electronic conductivity and ionic conductivity of the carbon shell coated on the outer surface of the active core are good, which can make up for the defect of poor conductivity of the phosphate-based active material, and can also regulate the size and morphology of the active core particles to improve the structural stability of the positive electrode material. The number and pore size of the mesopores on the outer surface of the carbon shell are lower than the number and pore size of the mesopores inside, and the outer surface of the carbon shell has fewer defects and fewer pores, which reduces the specific surface area, forms a more dense coating layer, and can more effectively prevent the electrolyte from passing through the carbon shell and contacting the active core, reduce the interface side reaction between the positive electrode material and the electrolyte, reduce the loss of lithium ions during the charge and discharge process, improve the constant power cycle stability of the positive electrode material, and improve the life and safety of the applied battery.

[0014] The second aspect of the present application provides a method for preparing a phosphate-based positive electrode material, which is obtained by sintering a phosphate-based precursor material under an inert atmosphere to obtain a core-shell structured product with a phosphate-based active semi-finished product doped with a plurality of metal cations as the core and a carbon shell layer as the coating layer. At this time, there are generally some oxygen-containing functional groups such as -OH on the surface or cross-section of the carbon-burned coating layer. After mixing it with another organic matter with a high oxygen content and sintering it under an inert atmosphere, the oxygen-containing functional groups such as -OH on the surface of the carbon-burned coating layer will react with the oxygen-rich functional groups in the oxygen-rich organic matter by dehydration condensation and the like. After the reaction, the organic matter remains on the surface of the carbon-burned shell layer, and is carbonized on the surface of the carbon-burned shell layer during the subsequent high-temperature sintering process to fill the gaps, fill and repair the inner carbon coating layer, and reduce the specific surface area, so that the number and pore size of the mesopores on the outer surface of the carbon shell layer in the prepared phosphate-based positive electrode material are lower than the number and pore size of the mesopores inside. On the one hand, doping with multiple metal ions improves crystal stability, enhances the stability of the phosphate-based active material, and increases the conduction rate of lithium ions inside the positive electrode material, which is beneficial to improving the constant power cycle stability of the positive electrode material. On the other hand, the outer surface of the carbon shell has fewer defects, fewer pores, and higher density, which can more effectively prevent the electrolyte from passing through the carbon shell and contacting the active core, reduce the interface side reactions between the positive electrode material and the electrolyte, reduce the loss of lithium ions during the charge and discharge process, improve the constant power cycle stability of the positive electrode material, and improve the life and safety of the applied battery.

[0015] The positive electrode sheet provided in the third aspect of the present application adopts the above-mentioned phosphate-based positive electrode material in the positive electrode active layer, and the phosphate-based positive electrode material includes a phosphate-based active core doped with multiple metal ions and a carbon shell layer whose number and pore size of mesopores on the outer surface are lower than that of the internal mesopores. This significantly improves the ionic conductivity, electronic conductivity, structural stability and other properties of the phosphate-based positive electrode material, while reducing the interfacial side reactions between the positive electrode material and the electrolyte, reducing the loss of lithium ions during the charging and discharging process, improving the constant power cycle stability of the positive electrode material, and improving the life and safety of the applied battery.

[0016] The secondary battery provided in the fourth aspect of the present application includes a positive electrode sheet with the above-mentioned electrochemical characteristics such as good stability, high energy density, good rate performance, and good cycle stability, thereby improving the electrochemical properties of the secondary battery such as energy density and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 It is a schematic diagram of a process for preparing a phosphate-based positive electrode material provided in an embodiment of the present application;

[0019] Figure 2 It is a cycle test chart of Examples 1 to 6 of the present application and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0022] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0023] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0024] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0025] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.

[0026] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0027] A first aspect of an embodiment of the present application provides a phosphate-based positive electrode material, including an active core and a carbon shell layer coated on the outer surface of the active core; wherein the active core contains a phosphate-based active material doped with multiple metal ions, and the number and pore size of mesopores on the outer surface of the carbon shell layer are lower than the number and pore size of mesopores inside.

[0028] The phosphate-based positive electrode material provided in the first aspect of the embodiment of the present application includes an active core and a carbon shell, wherein the active core contains a phosphate-based active material doped with a plurality of metal ions, and the doping of a plurality of metal ions can improve the crystal stability, enhance the stability of the phosphate-based active material body, and improve the conduction rate of lithium ions inside the positive electrode material, which is beneficial to improve the constant power cycle stability of the positive electrode material. The electronic conductivity and ionic conductivity of the carbon shell coated on the outer surface of the active core are good, which can make up for the defect of poor conductivity of the phosphate-based active material, and can also regulate the size and morphology of the active core particles to improve the structural stability of the positive electrode material. The number and pore size of the mesopores on the outer surface of the carbon shell are lower than the number and pore size of the mesopores inside, and the outer surface of the carbon shell has fewer defects and fewer pores, which reduces the specific surface area, forms a more dense coating layer, and can more effectively prevent the electrolyte from passing through the carbon shell and contacting the active core, reduce the interface side reaction between the positive electrode material and the electrolyte, reduce the loss of lithium ions during the charge and discharge process, improve the constant power cycle stability of the positive electrode material, and improve the life and safety of the applied battery.

[0029] In some possible implementations, the number of mesopores in the carbon shell decreases from the inside to the outside; in this case, the large number of internal mesopores can provide sufficient space for the core active material, and can serve as a buffer layer to buffer its volume deformation during the charge and discharge process, reduce the direct impact of external stress on the internal active material, and help improve the material's resistance to crushing and cycle stability. In addition, the rich mesoporous structure in the inner layer can shorten the transmission path of lithium ions inside the material, increase the diffusion rate of ions, and improve the ion transmission efficiency. The number of mesopores in the outer layer is relatively small, which can reduce the waste of external space while maintaining sufficient pores for electrolyte penetration to ensure good ion transmission. The decreasing design of the number of mesopores helps to form a uniform and dense solid electrolyte interface film on the surface of the material, which helps to reduce the decomposition of the electrolyte and the generation of by-products, and improve the coulombic efficiency. At the same time, this design also helps to improve the specific capacity and rate performance of the material, so that it can still maintain stable electrochemical performance at high current density.

[0030] In some possible implementations, the mesopore size of the outer surface of the carbon shell layer is 2nm to 4nm. In this case, the mesopore size of the outer surface of the carbon shell layer is small, which can more effectively prevent the electrolyte from passing through the carbon shell layer and contacting the active core, reduce the interfacial side reactions between the positive electrode material and the electrolyte, and improve the constant power cycle stability of the positive electrode material. Exemplarily, the mesopore size of the outer surface of the carbon shell layer can be 2nm, 3nm, 4nm, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0031] In some possible implementations, the mesopore size inside the carbon shell is 5nm to 20nm; in this case, the internal mesopore size is larger, which can provide sufficient space for the core active material, reduce the direct impact of external stress on the internal active material, and help improve the material's resistance to crushing and cycle stability. It can also shorten the transmission path of lithium ions inside the material, increase the diffusion rate of ions, and improve the ion transmission efficiency. Exemplarily, the mesopore size inside the carbon shell can be 5nm, 10nm, 15nm, 20nm, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0032] In some possible implementations, the thickness of the carbon shell layer is 5nm to 15nm. In this case, the thickness of the carbon shell layer can balance the transmission of lithium ions and the stability of the material, thereby maintaining a higher specific capacity. Exemplarily, the thickness of the carbon shell layer can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0033] In some possible implementations, the mass percentage of carbon material in the phosphate-based positive electrode material is 0.8% to 1.5%. In this case, the content of carbon material fully ensures the improvement of the conductivity and stability of the phosphate-based active material, while also ensuring that the phosphate-based positive electrode material has a higher capacity. Exemplarily, in the phosphate-based positive electrode material, the mass percentage of carbon material can be 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0034] In some possible implementations, the degree of graphitization on the outer surface of the carbon shell is lower than the degree of graphitization inside. In this case, the high degree of graphitization inside the carbon shell has a higher conductivity, which helps to improve the rate performance and low temperature performance of the phosphate-based positive electrode material. The highly conductive carbon coating layer can ensure the rapid transmission of lithium ions, reduce electrochemical polarization, and significantly improve the conductivity of the phosphate-based positive electrode material, reduce the internal resistance of the battery, and improve the charge and discharge efficiency of the battery. In addition, the degree of graphitization on the outer surface is lower than that on the inside, which can form a potential difference, which is conducive to the release and embedding of lithium ions.

[0035] In some possible implementations, the chemical formula of the phosphate-based active material is Li x Fe 1-y A yPO4, wherein A is selected from at least two of Ti, V, Mn, Cr, Ga, and Mg, 0.95≤x≤1.05, 0<y≤0.3. In this case, the phosphate active material is doped with at least two metal ions of Ti, V, Mn, Cr, Ga, and Mg. Different metal ion doping can play different performance optimization roles. For example, Mg (magnesium) doping plays the role of a skeleton inside the unit cell, which increases the unit cell volume and is conducive to deintercalation, but does not participate in the actual redox reaction, mainly stabilizing the unit cell, which is beneficial to the cycle performance. Ti (titanium) doping can not only increase the unit cell volume but also undergo redox reactions, provide electrons, and is beneficial to the rate performance of the material. However, when the valence state of Ti changes, the unit cell will change slightly, and the cycle stability is not as good as Mg. V (vanadium) doping can greatly improve and enhance the electrochemical properties of phosphate active materials. Through the appropriate vanadium doping ratio, a stable charge and discharge voltage platform and a large charge and discharge specific capacity can be obtained. The introduction of vanadium may also enhance the structural stability of the material, which helps to resist the volume change during the cycle, thereby extending the cycle life of the battery. The introduction of Mn (manganese) elements can reduce the drift and polarization of the battery under high temperature or high voltage conditions, thereby improving the cycle stability of the battery; the introduction of manganese can also increase the specific capacity of the battery, make the chemical stability of the positive electrode material better, increase the energy density of the battery, and enable the battery to store more electrical energy. Cr (chromium) doping can improve the conductivity of lithium iron phosphate materials, help improve the rate discharge performance of the material, and the improvement of conductivity can accelerate the transmission speed of lithium ions, thereby improving the charge and discharge efficiency of the battery; the introduction of chromium may also optimize the crystal structure of lithium iron phosphate and further improve its electrochemical properties. Ga (gallium) doping may help improve the ionic conductivity or electronic conductivity of lithium iron phosphate materials, thereby improving the electrochemical properties of the material. Therefore, by doping with a variety of metal ions, the crystal stability can be improved, the stability of the phosphate-based active material can be enhanced, and the conduction rate of lithium ions in the positive electrode material can be increased.

[0036] In some possible implementations, the particle size D50 of the active core is 200nm to 600nm. In this case, the particle size of the active core in the phosphate-based positive electrode material is conducive to ion deintercalation, improves the ion migration and transmission efficiency, and is also conducive to improving the tap density of the phosphate-based positive electrode material and improving the gram capacity of the phosphate-based positive electrode material. Exemplarily, the particle size D50 of the active core can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0037] In some possible implementations, the phosphate-based active material is doped with titanium ions and vanadium ions, or titanium ions and magnesium ions, or titanium ions and manganese ions, or manganese ions, titanium ions and vanadium ions, or manganese ions and chromium ions, or manganese ions and gallium ions. In these cases, doping the phosphate-based active material with these metal ions simultaneously can better improve the crystal stability, enhance the stability of the phosphate-based active material itself, increase the conduction rate of lithium ions in the positive electrode material, and improve the constant power cycle stability of the positive electrode material.

[0038] In some possible implementations, in the phosphate-based positive electrode material, the mass percentage of the phosphate-based active material is 98.9% to 99.8%. In this case, the mass percentage of the phosphate-based active material fully ensures the capacity of the phosphate-based positive electrode material, thereby ensuring that the applied battery has a higher energy density. Exemplarily, in the phosphate-based positive electrode material, the mass percentage of the phosphate-based active material can be 98.9%, 99.0%, 99.1%, 99.2%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0039] In a second aspect, the present invention provides a method for preparing a phosphate-based positive electrode material. Figure 1 As shown, the following steps are included:

[0040] S10. Obtaining a phosphate precursor material, performing a sintering treatment under an inert atmosphere to obtain a sintered product; a sintered product includes a phosphate active core semi-finished product doped with a plurality of metal ions and a sintered carbon shell;

[0041] S20. After mixing the calcined product with oxygen-rich organic matter, a secondary sintering treatment is performed under an inert atmosphere to obtain a phosphate-based positive electrode material including an active core and a carbon shell; the number and pore size of mesopores on the outer surface of the carbon shell are lower than the number and pore size of mesopores inside.

[0042] The preparation method of the phosphate-based positive electrode material provided in the second aspect of the embodiment of the present application is to sinter the phosphate-based precursor material under an inert atmosphere to obtain a core-shell structured product with a phosphate-based active semi-finished product doped with a plurality of metal cations as the core and a carbon shell layer as the coating layer. At this time, there are generally some oxygen-containing functional groups such as -OH on the surface or cross-section of the carbon-burned coating layer. After mixing it with another organic matter with a high oxygen content and sintering it under an inert atmosphere, the oxygen-containing functional groups such as -OH on the surface of the carbon-burned coating layer will react with the oxygen-rich functional groups in the oxygen-rich organic matter by dehydration condensation and the like. After the reaction, the organic matter remains on the surface of the carbon-burned shell layer, and is carbonized on the surface of the carbon-burned shell layer during the subsequent high-temperature sintering process to fill the gaps, fill and repair the inner carbon coating layer, and reduce the specific surface area, so that the number and pore size of the mesopores on the outer surface of the carbon shell layer in the prepared phosphate-based positive electrode material are lower than the number and pore size of the mesopores inside. On the one hand, doping with multiple metal ions improves crystal stability, enhances the stability of the phosphate-based active material, and increases the conduction rate of lithium ions inside the positive electrode material, which is beneficial to improving the constant power cycle stability of the positive electrode material. On the other hand, the outer surface of the carbon shell has fewer defects, fewer pores, and higher density, which can more effectively prevent the electrolyte from passing through the carbon shell and contacting the active core, reduce the interface side reactions between the positive electrode material and the electrolyte, reduce the loss of lithium ions during the charge and discharge process, improve the constant power cycle stability of the positive electrode material, and improve the life and safety of the applied battery.

[0043] In the above step S10:

[0044] In some possible implementations, a phosphate-based precursor material doped with a carbon source and multiple metal sources is prepared by a liquid phase method, and the preparation steps include: mixing and dissolving raw material components including a carbon source, multiple metal sources, a phosphorus source, a lithium source, and an iron source into an acidic solution, and drying to obtain a phosphate-based precursor material. In this case, the phosphate-based precursor material doped with a carbon source and multiple metal sources is prepared by a liquid phase method, which can improve the mixing and dispersion uniformity of each raw material component.

[0045] In some possible implementations, the acidic solution includes at least one of nitric acid, phosphoric acid, and hydrochloric acid with a concentration of 10% to 20%, and nitric acid solution is further preferred. In this case, the acidic solution has a relatively strong ability to digest the raw material components, making it easier to fully dissolve the precursor and form a solution with more uniform ion dispersion, which is conducive to the subsequent formation of phosphate-based positive electrode materials with good consistency and crystallinity. At the same time, the acidic solution is volatile and there will be no residue during the sintering process. Exemplarily, the concentration of the acidic solution can be 10%, 12%, 15%, 18%, 20%, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0046] In some possible implementations, the drying temperature is 60° C. to 80° C. Under such conditions, the solvent component in the precursor can be fully dried and removed. The drying temperature can be any typical but non-limiting point value such as 60° C., 65° C., 70° C., 75° C., 80° C., or an interval value between any two point values.

[0047] In some possible implementations, the inert gas is one of nitrogen and argon.

[0048] In some possible implementations, the metal source includes at least two of a titanium source, a vanadium source, a chromium source, a manganese source, a gallium source, and a magnesium source. In this case, doping a plurality of these metal ions in the phosphate-based active material can improve the crystal stability, enhance the stability of the phosphate-based active material, and increase the conduction rate of lithium ions in the positive electrode material.

[0049] In some possible implementations, the mass percentage of the metal source in the raw material component is 0.5% to 5%; in this case, the amount of the metal source added can avoid the problem of excessive addition leading to the formation of impurities, which is not conducive to the intrinsic performance of the phosphate-based active material. Exemplarily, the mass percentage of the metal source in the raw material component can be 0.5%, 1%, 2%, 3%, 4%, 5%, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0050] In some possible implementations, the titanium source includes one of tetrabutyl titanate, tetraethyl titanate, etc. In some embodiments, the molar ratio of the titanium source to the iron source is (0-0.15):1.

[0051] In some possible implementations, the vanadium source includes at least one of vanadium nitrate and vanadium acetate.

[0052] In some possible implementations, the chromium source includes at least one of chromium oxide, chromium sulfate, and chromium nitrate.

[0053] In some possible implementations, the manganese source includes at least one of manganese sulfate, manganese nitrate, manganese acetate, and manganese oxide.

[0054] In some possible implementations, the gallium source includes at least one of gallium oxide, gallium sulfate, and gallium nitrate.

[0055] In some possible implementations, the magnesium source includes at least one of magnesium nitrate, magnesium sulfate, and magnesium acetate.

[0056] In some possible implementations, the carbon source includes at least one of glucose, polyethylene glycol, sucrose, and fructose. In this case, these carbon sources can form a stable carbon coating layer in the subsequent burning process, and the low oxygen content is conducive to the formation of phosphate-based active material crystals. If the carbon source also uses oxygen-rich organic matter in the burning process, due to the high oxygen content, the amount of oxygen-rich organic matter used in the burning process for the same finished product carbon content is greater than that of these carbon sources with less oxygen content, and the large amount of oxygen-rich organic matter used in the burning process is not conducive to the formation of phosphate-based active material crystals, and the phosphate-based active material can generate better crystals under anaerobic conditions.

[0057] In some possible implementations, the mass of the carbon source is 1% to 20% of the total mass of the phosphorus source, lithium source and iron source. In this case, the addition ratio of the carbon source is 1% to 20% of the sum of the mass of the lithium source, iron source and phosphorus source, which fully ensures that the carbon source is dehydrated and condensed during the burning process, and carbonized to form a carbon coating layer. Exemplarily, the mass of the carbon source is 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20% of the total mass of the phosphorus source, lithium source and iron source, and other typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0058] In some possible implementations, the lithium source includes one or more of lithium acetate, lithium nitrate, lithium carbonate, and lithium hydroxide.

[0059] In some possible implementations, the iron source includes ferric acetate, ferric nitrate, ferric sulfate, and the like.

[0060] In some possible implementations, the phosphorus source includes ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and the like.

[0061] In some possible implementations, the molar ratio of the phosphorus source, the iron source, and the lithium source is 1: (0.7-1.0): (1-1.05). In this case, it is beneficial for the phosphorus source, the iron source, and the lithium source to form phosphate-based activity under high-temperature sintering conditions, thereby reducing the generation of impurity by-products. Exemplarily, the molar ratio of the phosphorus source, the iron source, and the lithium source can be 1:0.7:1, 1:0.8:1, 1:0.9:1, 1:1:1.05, and other typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0062] In some possible implementations, the heating rate of a sintering treatment is 2°C / min to 5°C / min, the temperature condition is 400°C to 600°C, and the duration is 4h to 10h. Under such sintering conditions, the iron source and the phosphorus source first form iron phosphate crystallites, and then grow, while lithium ions are embedded to form lithium iron phosphate; the carbon source dehydrates, condenses, and carbonizes to form a carbon coating. Among them, the sintering temperature fully ensures that the phosphate-based active material has better crystallinity, more complete crystal form, larger particles, and a higher degree of graphitization of the carbon source.

[0063] Exemplarily, the heating rate of a sintering treatment can be any typical but non-limiting point value such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, or an interval value between any two point values; the temperature can be any typical but non-limiting point value such as 400°C, 450°C, 500°C, 550°C, 600°C, or an interval value between any two point values; the duration can be any typical but non-limiting point value such as 4h, 5h, 6h, 7h, 8h, 9h, 10h, or an interval value between any two point values.

[0064] In the above step S20:

[0065] In some possible implementations, the oxygen-rich organic matter includes at least one of glutamic acid, malic acid, glycine, ascorbic acid, and maleic acid. In this case, these oxygen-rich organic matter contain abundant oxygen-containing functional groups such as carboxyl, which can react with oxygen-containing functional groups such as -OH on the surface or cross section of the carbon-burned coating layer by dehydration condensation, etc. After the reaction, the organic matter remains on the surface of the carbon-burned shell layer, and carbonizes on the surface of the carbon-burned shell layer during the subsequent high-temperature sintering process to fill the gaps, fill and repair the outer surface of the carbon coating layer, and reduce the specific surface area, so that the number and pore size of the mesopores on the outer surface of the carbon shell layer in the prepared phosphate-based positive electrode material are lower than the number and pore size of the mesopores inside.

[0066] In some possible implementations, the mass ratio of oxygen-rich organic matter to the calcined product is (0.5% to 10%): 1. In this case, the filling and repair of pores and defects in the calcined carbon shell by oxygen-rich organic matter is fully ensured, the number and pore size of mesopores on the surface of the carbon shell are reduced, the density of the surface of the carbon shell is improved, and it is ensured that the electrolyte can be effectively blocked from passing through the carbon shell to contact the active core, reducing the interface side reaction between the positive electrode material and the electrolyte, and improving the constant power cycle stability of the positive electrode material. And this amount avoids the formation of an excessively thick carbon layer and reduces the capacity of the phosphate-based positive electrode material. Exemplarily, the mass ratio of oxygen-rich organic matter to the calcined product can be 0.5%: 1, 1%: 1, 3%: 1, 5%: 1, 8%: 1, 10%: 1, typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0067] In some possible implementations, the heating rate of the secondary sintering treatment is 2°C / min to 5°C / min, the temperature condition is 400°C to 700°C, and the duration is 4h to 24h. In this case, the secondary sintering treatment is carried out, and the oxygen-containing functional groups such as -OH on the surface of the carbon-burned coating layer will undergo dehydration condensation and other reactions with the oxygen-rich functional groups in the oxygen-rich organic matter. After the reaction, the organic matter remains on the surface of the carbon-burned shell layer. In the subsequent high-temperature sintering process, it is carbonized on the surface of the carbon-burned shell layer to fill the gaps, fill and repair the inner carbon coating layer, reduce the specific surface area, and make the number and pore size of the mesopores on the outer surface of the carbon shell layer in the prepared phosphate-based positive electrode material lower than the number and pore size of the mesopores inside.

[0068] Exemplarily, the heating rate of the secondary sintering treatment can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., any typical but non-limiting point value, or an interval value between any two point values; the temperature can be 400°C, 500°C, 600°C, 700°C, etc., any typical but non-limiting point value, or an interval value between any two point values; the duration can be 4h, 8h, 12h, 16h, 20h, 24h, etc., any typical but non-limiting point value, or an interval value between any two point values.

[0069] In some possible implementations, the inert gas is one of nitrogen and argon.

[0070] In a third aspect, an embodiment of the present application provides a positive electrode sheet, including a current collector and a positive electrode active layer formed on the surface of the current collector, wherein the positive electrode active layer contains the above-mentioned phosphate-based positive electrode material.

[0071] The positive electrode sheet of the embodiment of the present application adopts the above-mentioned phosphate-based positive electrode material in the positive electrode active layer, and the phosphate-based positive electrode material includes a phosphate-based active core doped with multiple metal ions and a carbon shell layer whose number and pore size of mesopores on the outer surface are lower than that of the internal mesopores. This significantly improves the ionic conductivity, electronic conductivity, structural stability and other properties of the phosphate-based positive electrode material, while reducing the interfacial side reactions between the positive electrode material and the electrolyte, reducing the loss of lithium ions during the charging and discharging process, improving the constant power cycling stability of the positive electrode material, and improving the life and safety of the applied battery.

[0072] In some possible implementations, the preparation of the positive electrode active layer includes the steps of: mixing the above-mentioned phosphate-based positive electrode material, conductive agent and binder to form an electrode slurry, coating the electrode slurry on a current collector, and preparing a positive electrode sheet through steps such as drying, rolling and die cutting.

[0073] In some possible implementations, the mass percentage of the phosphate-based positive electrode material in the positive electrode active layer of the positive electrode sheet is 90% to 95%. Specifically, the mass percentage of the phosphate-based positive electrode material in the positive electrode active material layer can be 90%, 91%, 92%, 93%, 94%, 95%, etc.

[0074] In some possible implementations, the current collector of the positive electrode sheet includes but is not limited to any one of copper foil and aluminum foil.

[0075] In some possible implementations, the content of the binder in the active material layer of the positive electrode sheet is 2 wt% to 5 wt%. In specific embodiments, the content of the binder can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.

[0076] In some possible implementations, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.

[0077] In some possible implementations, the content of the conductive agent in the active material layer of the positive electrode sheet is 1 wt% to 5 wt%. In specific embodiments, the content of the conductive agent can be 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.

[0078] In some possible implementations, the conductive agent includes graphite, carbon black, acetylene black, graphene, carbon fiber, C 60 and one or more of carbon nanotubes.

[0079] In a fourth aspect, an embodiment of the present application provides a secondary battery, wherein the secondary battery comprises the above-mentioned positive electrode sheet.

[0080] The secondary battery provided in the embodiment of the present application includes a positive electrode sheet with the above-mentioned electrochemical characteristics such as good stability, high energy density, good rate performance, and good cycle stability, thereby improving the electrochemical properties of the secondary battery such as energy density and cycle stability.

[0081] The present application does not specifically limit the negative electrode sheet, electrolyte, separator, etc. in the secondary battery of the embodiment, and can be applied to any battery system.

[0082] In some possible implementations, the negative electrode active material of the secondary battery includes, but is not limited to, carbon materials such as graphite, soft carbon (such as coke), hard carbon, or nitrides, tin-based oxides, tin-based oxides, tin alloys, and nano-negative electrode materials, etc. The current collector includes, but is not limited to, any one of copper foil and aluminum foil.

[0083] In some possible embodiments, the steps of making the negative electrode sheet include: mixing the negative electrode active material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to make a positive electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining a negative electrode sheet after rolling, slitting, and die-cutting.

[0084] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).

[0085] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.

[0086] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.

[0087] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as lithium-air batteries and lithium metal batteries.

[0088] In some possible implementations, the battery cells of the present application can be assembled into a battery module, and the battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module. The battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.

[0089] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0090] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in the performance of the phosphate-based positive electrode material and the preparation method thereof in the embodiments of the present application, the above technical solution is illustrated by means of multiple embodiments below.

[0091] Example 1

[0092] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0093] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 10% of the total weight of the solid glucose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 5% of its weight of glutamic acid in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations having good stability was prepared.

[0094] Example 2

[0095] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0096] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 20% of the total weight of the solid glucose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 5% of its weight of glutamic acid in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations having good stability was prepared.

[0097] Example 3

[0098] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0099] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, vanadium oxide, and manganese nitrate are dissolved in 10wt% dilute nitric acid according to a molar ratio of 0.98:1:1.05:0.01:0.01:0.2, and then 10% of the total weight of glucose is added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a semi-finished product of Ti, V, and Mn doped lithium iron phosphate is prepared. The semi-finished product is mixed with 5% of its weight of glutamic acid in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a composite carbon-coated lithium manganese iron phosphate doped with multiple cations having good stability is prepared.

[0100] Example 4

[0101] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0102] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 10% of the total weight of the solid glucose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 10% of its weight of glutamic acid in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations having good stability was prepared.

[0103] Example 5

[0104] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0105] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 10% of the total weight of the solid glucose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a Ti, V-doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 11% of glutamic acid by weight in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations having good stability was prepared.

[0106] Example 6

[0107] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0108] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 10% of the total weight of the solid glucose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 5% of its weight of glycine in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations having good stability was prepared.

[0109] Comparative Example 1

[0110] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0111] First, ferrous acetate, ammonium dihydrogen phosphate, and lithium acetate in a molar ratio of 0.99:1:1.05 were dissolved in 15wt% dilute nitric acid, stirred for 4 hours, dried, placed in a tubular furnace, heated to 600°C at a heating rate of 4°C / min in an inert atmosphere for 6 hours to prepare a semi-finished lithium iron phosphate. The semi-finished product was mixed with 3% of glucose by weight in a high-speed mixer and ground into powder, placed in a tubular furnace, heated to 680°C at a heating rate of 5°C / min in a nitrogen atmosphere for 16 hours to prepare a carbon-coated lithium iron phosphate.

[0112] Comparative Example 2

[0113] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0114] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 10% of the total weight of the solid glucose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 550°C at a heating rate of 5°C / min under an inert atmosphere for 6 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 3% of its weight of glucose in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min under a nitrogen atmosphere for 15 hours, and a variety of cation-doped lithium iron phosphates were prepared.

[0115] Comparative Example 3

[0116] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0117] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.97:1:1.05:0.02:0.01, and then 15% of the total weight of sucrose was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 580°C at a heating rate of 3°C / min under an inert atmosphere for 4 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 3% of glucose by weight in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 680°C at a heating rate of 5°C / min under a nitrogen atmosphere for 16 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations was prepared.

[0118] Comparative Example 4

[0119] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0120] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, stirred for 4 hours, dried, placed in a tubular furnace, heated to 580°C at a heating rate of 3°C / min in an inert atmosphere for 4 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 5% of its weight of glutamic acid in a high-speed mixer and ground into powder, placed in a tubular furnace, heated to 680°C at a heating rate of 5°C / min in a nitrogen atmosphere for 16 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations was prepared.

[0121] Comparative Example 5

[0122] A phosphate-based positive electrode material, the preparation of which comprises the following steps:

[0123] First, ferric nitrate, ammonium dihydrogen phosphate, lithium nitrate, tetrabutyl titanate, and vanadium oxide were dissolved in 10wt% dilute nitric acid at a molar ratio of 0.98:1:1.05:0.01:0.01, and then 5% of the total weight of the solid glutamic acid was added thereto, stirred for 4 hours, dried, placed in a tubular furnace, heated to 580°C at a heating rate of 3°C / min under an inert atmosphere for 4 hours, and a Ti and V doped lithium iron phosphate semi-finished product was prepared. The semi-finished product was mixed with 10% of its weight of glucose in a high-speed mixer, ground into powder, placed in a tubular furnace, heated to 680°C at a heating rate of 5°C / min under a nitrogen atmosphere for 16 hours, and a composite carbon-coated lithium iron phosphate doped with multiple cations was prepared.

[0124] The key raw material components and contents in the above examples and comparative examples are shown in Table 1 below:

[0125] Table 1

[0126]

[0127]

[0128] Further, in order to verify the progress of the embodiments of the present application, the phosphate-based positive electrode materials prepared in the above embodiments and comparative examples were subjected to the following tests:

[0129] 1. Mesopore diameter on the surface of carbon shell: Scan the particle cross section with a scanning electron microscope to calculate the diameter of the pores on the surface of the carbon shell;

[0130] 2. Mesopore diameter inside the carbon shell: Scan the particle cross section using a scanning electron microscope to calculate the diameter of the pores inside the carbon shell;

[0131] 3. The number of mesopores on the surface of the carbon shell is lower than that inside the shell: the particle cross section is scanned by scanning electron microscopy for statistical calculation;

[0132] 4. Ionic conductivity test: Use a carbon powder resistivity tester to test the material powder resistance. Resistance and ionic conductivity are reciprocals of each other and can be calculated.

[0133] The above test results are shown in Table 2 below:

[0134] Table 2

[0135]

[0136]

[0137] It can be seen from the above test results that after the calcined product is obtained in the embodiment of the present application, it is mixed with oxygen-rich organic matter and sintered under an inert atmosphere. The oxygen-containing functional groups such as -OH on the surface of the calcined carbon coating layer will react with the oxygen-rich functional groups in the oxygen-rich organic matter by dehydration condensation and other reactions. After the reaction, the organic matter remains on the surface of the calcined carbon shell layer, filling and repairing the carbon coating layer, reducing the specific surface area, so that the number and pore size of the mesopores on the outer surface of the carbon shell layer in the prepared phosphate-based positive electrode material are lower than the number and pore size of the mesopores inside. The outer surface of the carbon shell layer has fewer defects, fewer pores, and higher density, which can better reduce interface side reactions. In addition, the crystal stability of the positive electrode material is improved by doping with a variety of metal ions, the stability of the material body is enhanced, and the conduction rate of lithium ions is improved.

[0138] Furthermore, the above-mentioned embodiments and comparative examples were applied to lithium-ion batteries, and electrochemical performance tests were performed respectively. The preparation process of the lithium-ion battery is as follows:

[0139] ① Preparation of positive electrode sheet: According to the mass ratio, the phosphate positive electrode material of the embodiment or comparative example: SP: PVDF: NMP = 93.5: 2.5: 4: 100, the ball mill stirrer is stirred at a speed of 360 rpm for 1 hour to mix evenly to obtain positive electrode slurry. The prepared positive electrode slurry is poured on aluminum foil and evenly scraped with a scraper. The positive electrode sheet is dried in an oven at 120°C for 20 minutes, and then rolled at a pressure of 10 MPa to obtain a positive electrode sheet.

[0140] ② The battery assembly process is as follows: the prepared positive electrode plate is attached to the positive electrode metal shell with conductive adhesive, and then dried; the metal lithium sheet is used as the negative electrode, the Celgard2400 microporous membrane is used as the battery separator, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) containing 1.0M LiPF6 is used as the electrolyte (EC / DEC volume ratio is 1:1), and the button battery is assembled in a glove box to obtain a lithium-ion button battery.

[0141] The lithium-ion batteries assembled in the above examples and comparative examples were subjected to constant power cycle performance tests under the following test conditions: 200 cycles at 0.5P at 60°C. The test results are shown in the attached figure. Figure 2 As shown, attached Figure 2 It is a cycle test diagram of Examples 1 to 6 and Comparative Examples 1 to 5.

[0142] By the attached Figure 2 It can be seen from the test results that after the second sintering with oxygen-rich organic matter in the embodiment of the present application, the density of the carbon coating layer can be increased, the direct contact between the material and the electrolyte can be reduced, the occurrence of side reactions can be reduced, and the loss of lithium ions during the charging and discharging process can be reduced, which significantly improves the constant power cycle stability of the positive electrode material and improves the life and safety of the applied battery.

[0143] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A phosphate-based positive electrode material, characterized in that: It comprises an active core and a carbon shell layer coated on the outer surface of the active core; wherein the active core contains a phosphate-based active material doped with a variety of metal ions, and the number and pore size of mesopores on the outer surface of the carbon shell layer are lower than the number and pore size of mesopores inside.

2. The phosphate-based positive electrode material according to claim 1, characterized in that: The carbon shell layer has at least one of the following characteristics (1) to (5): (1) The number of mesopores decreases from the inside to the outside; (2) The mesopore size of the outer surface is 2nm to 4nm; (3) The internal mesopore size is 5nm to 20nm; (4) Thickness: 5 nm to 15 nm; (5) The degree of graphitization on the outer surface is lower than that on the inner surface.

3. The phosphate-based positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the phosphate active material is Li x Fe 1-y A y PO4, wherein A is selected from at least two of Ti, V, Mn, Cr, Ga, and Mg, 0.95≤x≤1.05, 0<y≤0.3; And / or, the particle size D50 of the active core is 200nm to 600nm.

4. The phosphate-based positive electrode material according to claim 3, characterized in that: The phosphate active material is doped with titanium ions and vanadium ions, or titanium ions and magnesium ions, or titanium ions and manganese ions, or manganese ions, titanium ions and vanadium ions, or manganese ions and chromium ions, or manganese ions and gallium ions; And / or, in the phosphate-based positive electrode material, the mass percentage of carbon material is 0.8% to 1.5%; And / or, in the phosphate-based positive electrode material, the mass percentage of the phosphate-based active material is 98.9% to 99.8%.

5. A method for preparing a phosphate-based positive electrode material, characterized in that: The following steps are involved: Obtaining a phosphate precursor material, and performing a sintering treatment under an inert atmosphere to obtain a sintered product; the sintered product includes a phosphate active core semi-finished product doped with multiple metal ions and a sintered carbon shell; After the calcined product is mixed with oxygen-rich organic matter, a secondary sintering treatment is performed under an inert atmosphere to obtain a phosphate-based positive electrode material including an active core and a carbon shell; the number and pore size of mesopores on the outer surface of the carbon shell are lower than the number and pore size of mesopores inside.

6. The method for preparing a phosphate-based positive electrode material according to claim 5, characterized in that: The preparation steps of the phosphate precursor material include: mixing and dissolving raw material components including a carbon source, multiple metal sources, a phosphorus source, a lithium source and an iron source into an acidic solution, and drying to obtain the phosphate precursor material; And / or, the heating rate of the primary sintering treatment is 2°C / min to 5°C / min, the temperature condition is 400°C to 600°C, and the duration is 4h to 10h; And / or, the metal source includes at least two of a titanium source, a vanadium source, a chromium source, a manganese source, a gallium source, and a magnesium source; And / or, the carbon source includes at least one of glucose, polyethylene glycol, sucrose and fructose.

7. The method for preparing a phosphate-based positive electrode material according to claim 6, wherein: In the raw material components, the mass percentage of the metal source is 0.5% to 5%; and / or, the molar ratio of the phosphorus source, the iron source and the lithium source is 1:(0.7-1.0):(1-1.05); And / or, the mass of the carbon source is 1% to 20% of the total mass of the phosphorus source, the lithium source and the iron source; And / or, the acidic solution includes at least one of nitric acid, phosphoric acid and hydrochloric acid with a concentration of 10% to 20%; And / or, the drying temperature is 60°C to 80°C.

8. The method for preparing a phosphate-based positive electrode material according to any one of claims 5 to 7, characterized in that: The oxygen-rich organic matter includes at least one of glutamic acid, malic acid, glycine, ascorbic acid, and maleic acid; And / or, the mass ratio of the oxygen-rich organic matter to the calcined product is (0.5% to 10%): 1; And / or, the heating rate of the secondary sintering treatment is 2°C / min to 5°C / min, the temperature condition is 400°C to 700°C, and the duration is 4h to 24h.

9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active layer formed on the surface of the current collector, wherein the positive electrode active layer contains the phosphate-based positive electrode material as claimed in any one of claims 1 to 4, or the phosphate-based positive electrode material prepared by the method as claimed in any one of claims 5 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in claim 9.